Novel resorbable bone wax containing β-TCP and starch microspheres for accelerating bone hemostasis and promoting regeneration - Duan, Qiangqiang; Liu, Huiling; Zheng, Lixia; Cai, Daozhang; Huang, Guangxin; Liu, Yu; Guo, Rui (Frontiers in Bioengineering and Biotechnology, 2023)
Traditional non-resorbable bone wax has been used in clinical surgery for more than 100 years. However, residual bone wax has been proven to cause numerous complications. In this study, a novel resorbable bone wax was designed to overcome the disadvantages of traditional non-resorbable bone wax. Alkylene oxide copolymers were used as the main component of resorbable bone wax; additionally, β-tricalcium phosphate and starch microspheres were added to enhance bone regeneration and hemostatic ability. This novel resorbable bone wax has a high potential for clinical translation and is expected to be developed as a substitute for traditional bone wax.